Respuesta :

Answer:

population of 1st city =660,000

Step-by-step explanation:

Let the population of second city be x

given that

population of the first city is equal to 32% of the population of the second city

Therefore

population of 1st city = 32% of the population of the second city

                                   32% of x = (32/100)*x

total population of two cities = x + (32/100)*x = (100x+32x)/100 = 132x/100

Also, population of two cities = 660000

thus,

132x/100 =  660000

=> 132x =  660000*100 =  66000000

=> x = 66000000/132 = 2,062,500

Thus, population of 2nd city is 2,062,500

population of 1st city = (32/100)*x = 32/100 * 2,062,500 = 660,000